(3QSGdI aj JaUjd eG bjd aj CHhj GdQShd Udi Gddg Ydjg hSdes - (3GdJhbGOj GdESJGfHhdj GdYKeGfj GdMfaj, GHf ceGd HGTG, ceGd HGTG RGOg, TeS GdOjf, CMeO Hf SdjeGf Hf ceGd HGTG, (B940 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj cQe BOe Ydjg GdSdGe (B() (3hGdUdGI Ydi ef NUg Gddg JYGdi HWgGQI GdfSH hMaX BHGFg ef GdOfS JYXjeG dTCfgGYde Cf GdSda GNJdahG Cf CHhj GdfHj Ydjg GdSdGe gd eGJG Ydi GdcaQ Ce dG? aPgH Edi GdChd LeY efge UGMH GdJjSjQ MjK bGd aj JaSjQ bhdg JYGdi (B{(3hdG JSCd Yf CUMGH GdLMje(B}s
(3BNQgG (B:s
(3aMb GdeSde Cf jeSc dSGfg YeG jMd HTQa fSH fHjfG Ydjg GdSdGe HhLg ef GdhLhg hdG NaGA aj EKHGJ GdTQc aj CHhjg ENdGd XGgQ HTQa fSHg GdWGgQ hHGdLedI agPg GdeSCdI djSJ ef GdGYJbGOGJ adG MX ddbdH efgG hCeG GddSGf aMbg YeG jJHGOQ Yfg GdfbUGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 133s
(3eYLe GdeDdajf(B: 3 /148s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs